Efficacy and Safety of Sitagliptin for the Treatment of New-Onset Diabetes after Renal Transplantation - Brian P. Boerner; Clifford D. Miles; Vijay Shivaswamy (International Journal of Endocrinology)
New-onset diabetes after transplantation (NODAT) is a common comorbidity after renal transplantation. Though metformin is the first-line agent for the treatment of type 2 diabetes, in renal transplant recipients, metformin is frequently avoided due to concerns about renal dysfunction and risk for lactic acidosis. Therefore, alternative first-line agents for the treatment of NODAT in renal transplant recipients are needed. Sitagliptin, a dipeptidyl-peptidase-4 (DPP-4) inhibitor, has a low incidence of hypoglycemia, is weight neutral, and, in a small study, did not affect immunosuppressant levels. However, long-term sitagliptin use for the treatment of NODAT in kidney transplant recipients has not been studied. We retrospectively analyzed renal transplant recipients diagnosed with NODAT and treated with sitagliptin to assess safety and efficacy. Twenty-two patients were started on sitagliptin alone. After 12 months of followup, 19/22 patients remained on sitagliptin alone with a significant improvement in hemoglobin A1c. Renal function and immunosuppressant levels remained stable. Analysis of long-term followup (32.5 ± 17.8 months) revealed that 17/22 patients remained on sitagliptin (mean hemoglobin A1c < 7%) with 9/17 patients remaining on sitagliptin alone. Transplant-specific adverse events were rare. Sitagliptin appears safe and efficacious for the treatment of NODAT in kidney transplant recipients.